OPTIMASI PARAMETER PROSES 3D PRINTING FDM TERHADAP KEKUATAN TARIK FILAMENT ABS CCTREE MENGGUNAKAN METODE TAGUCHI L9 - ade Ferdiansyah; Pristiansyah Pristiansyah; Boy Rollastin (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
3D Printing is an additive manufacturing technique that can be used to convert computer aided design (CAD) data and then print it by adding material layer by layer to form a 3D product. One technique or method that is often used in 3D Printing technology is FDM (Fused Deposition Modeling), because this technique is the easiest to use and the cheapest. The purpose of this study was to obtain the optimal process parameters on 3D Printing FDM to the resulting tensile strength. This study uses the Taguchi method with an experimental design used L9 (34) OA. The material used in this research is ABS CCTREE. The process parameters used in this research are nozzle temperature (°C), table temperature (°C), layer thickness (mm) and print speed (mm/s). The strongest tensile strength value is 41 Mpa. Parameters that produce the strongest quality are performed at table temperature (92 °C), nozzle temperature (237 °C), layer thickness (0.22 mm) and Print speed (42 mm/s).